Hellboy - Gordon, Lawrence 1936-; Richardson, Mike 1950-; Levin, Lloyd; Toro, Guillermo del 1964-; Perlman, Ron 1950-; Blair, Selma 1972-; Tambor, Jeffrey 1944-; Roden, Karel 1962-; Evans, Rupert; Steele, Brian; Jones, Doug 1960-; Hurt, John 1940-; et al.
In the 1940s, the Third Reich has joined forces with the evil Grigori Rasputin, who has used his occult powers to summon up a demon from the depths of Hell. However, the demonic creature is captured by American forces, and put in the care of Professor Broom. Under Broom's care, Hellboy develops the desire to do good. Sixty years later he takes action as part of an elite secret defense team alongside Liz Sherman, and Abe Sapian, an aquatic humanoid with the power of telepathy. Hellboy finds himself facing the powerful Rasputin determined to bring the demon back to the forces of darkness.